Layer-by-layer fabrication of fluorescent microspheres using micelles as a spacer: simultaneously realizing fluorescence enhancement and introduction of bioconjugation sites. Issue 5 (19th January 2018) - Sun, Lijuan; Qiu, Tian; Liu, Jiangxin; Miao, Ke; Zhao, Youliang; Fan, Li-Juan
Abstract : Fluorescent microspheres fabricated using a conjugated polymer and micelles are demonstrated to have strong emission and are effective for bioconjugation. Abstract : The combination of fluorescence properties and other functions can significantly enhance the multipurpose applications of functional materials. Herein, fluorescent microspheres with strong fluorescence and bioconjugation sites were prepared via the layer-by-layer (LBL) introduction of poly( p -phenylene vinylene) (PPV) with micelles as a spacer on the substrate spheres. At first, the diblock copolymer poly(acrylic acid)- block -polystyrene (PAA- b -PS) was synthesized and assembled into micelles (PSAm) with the carboxylic groups facing outward. Then, the negatively charged PSAm and positively charged PPV polymer precursor (pre-PPV) were alternately introduced into the substrate polystyrene-divinylbenzene microspheres with sulfonic groups on the surface (SPSDVB) followed by thermal elimination to obtain fluorescent SPSDVB-(PPV/PSAm) n microspheres by converting pre-PPV into PPV. The spheres were found to have stable and bright fluorescence with a very clear core–shell structure. The mechanism for fluorescence enhancement with PSAm as the spacer was studied, and the capability for bioconjugation was also demonstrated. This study provides a promising general strategy for the preparation of fluorescent microspheres combining strong emission with different functional groups to meet various applications.